2021
DOI: 10.1097/rlu.0000000000003702
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 99mTc-PSMA to 99mTc-MDP in Prostate Cancer Staging of the Skeletal System

Abstract: Purpose This prospective study was aimed at assessing the ability of 99m Tc-PSMA scan to detect bone metastases in prostate cancer (PCa) against 99m Tc-MDP scan as a standard and assess the correlation of these modalities in PCa staging of bone involvement. Patients and Methods Forty-one patients (41) with histologically confirmed PCa were scanned using both methods. Planar imaging was performed with additional regional SPECT/CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…In this study, 99m Tc-PSMA SPECT/CT and 99m Tc-MDP SPECT/CT were systematically compared using the SPECT/CT imaging mode. Few studies have compared 99m Tc-PSMA SPECT/CT and 99m Tc-MDP SPECT/CT in the detection of PCa bone metastases 11 , 12 ; only one prospective study, reported by Kabunda et al and including 41 patients, has been published 12 . In contrast to previously reported studies, our study was not only a head-to-head prospective study but also analysed the relationship of bone metastasis size and serum PSA level on the detection rate of bone metastases in the two imaging modes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 99m Tc-PSMA SPECT/CT and 99m Tc-MDP SPECT/CT were systematically compared using the SPECT/CT imaging mode. Few studies have compared 99m Tc-PSMA SPECT/CT and 99m Tc-MDP SPECT/CT in the detection of PCa bone metastases 11 , 12 ; only one prospective study, reported by Kabunda et al and including 41 patients, has been published 12 . In contrast to previously reported studies, our study was not only a head-to-head prospective study but also analysed the relationship of bone metastasis size and serum PSA level on the detection rate of bone metastases in the two imaging modes.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and targeted treatment can effectively improve the prognosis. 4,5 The use of radioactive drugs to alleviate bone pain has advantages, including the simultaneous treatment of multiple metastatic lesions, repeatability, and combination with other therapies. 6,7 Bisphosphonates have been used in the treatment of bone metastases with good results.…”
mentioning
confidence: 99%
“…Bone is the most common metastatic site in patients with prostate cancer. Early diagnosis and targeted treatment can effectively improve the prognosis 4,5 . The use of radioactive drugs to alleviate bone pain has advantages, including the simultaneous treatment of multiple metastatic lesions, repeatability, and combination with other therapies 6,7 .…”
mentioning
confidence: 99%
“…Prostate cancer is a global health issue and is the most commonly diagnosed cancer in men worldwide. 1,2 After radical prostatectomy 3 or radiotherapy for primary treatment of prostate cancer, up to 50% of all men develop tumor recurrence, which is determined by rising PSA levels. 468 Ga-labeled ligands targeting PSMA have been used with extraordinary success for PET imaging of prostate cancer.…”
mentioning
confidence: 99%
“…Prostate-specific antigen level decreased following surgery (to 2.5 ng/dL). Prostate cancer is a global health issue and is the most commonly diagnosed cancer in men worldwide 1,2 . After radical prostatectomy 3 or radiotherapy for primary treatment of prostate cancer, up to 50% of all men develop tumor recurrence, which is determined by rising PSA levels 4 .…”
mentioning
confidence: 99%